How well will you FIT? Use of a modified MMI to assess applicants' compatibility with an emergency medicine residency program. Issue 1 (1st January 2016) - Min, Alice A.; Leetch, Aaron; Nuño, Tomas; Fiorello, Albert B.
Abstract : Purpose: Emergency medicine residency programs have evaluated the use of Multiple Mini Interviews (MMIs) for applicants. The authors developed an MMI-style method called the Fast Interview Track (FIT) to predict an applicant's 'fit' within an individual residency program. Methods: Applicants meet with up to five residents and are asked one question by each. Residents score the applicant using a Likert scale from 1 to 5 on two questions: 'How well does the applicant think on his/her feet?' and 'How well do you think the applicant will fit in here?'. To assess how well these questions predicted a resident's 'fit', current residents scored fellow residents on these same questions. These scores were compared with the residents' interview FIT scores. A postmatch survey of applicants who did not match at this program solicited applicants' attitudes toward the FIT sessions. Results: Among the junior class, the correlation between interview and current scores was significant for question 1 (rho=0.5192 [ p= 0.03]) and question 2 (rho=0.5753 [ p= 0.01]). Among seniors, Spearman's rho was statistically significant for question 2, though not statistically significant for question 1. The chi-square measure of high scores (4–5) versus low scores (1–3) found a statistically significant association between interview and current scores for interns and juniors. Of the 29 responses to the postmatch survey, 16 (55%) felt FIT sessions provided a good sense of the program's personality and only 6 (21%) disagreed. Nine (31%) felt FIT sessions positively impacted our program's ranking and 11 (38%) were 'Neutral'. Only two (7%) reported that FIT sessions negatively impacted their ranking of our program. Conclusions: FIT provided program leadership with a sense of an applicant's 'fit' within this program. Interview day scores correlated with scores received during residency. Most applicants report a positive experience with FIT sessions. FIT provides a useful tool to recruit applicants who fit with the residency program.